SUSTAINABLE PALLIATIVE PROGRAMMES FOR REDUCING THE IMPACT OF CORONA VIRUS PANDEMIC ON FOOD INSECURITY OF CROP FARMERS IN TARABA STATE, NIGERIA - Fagam, A. S. (Nigerian Journal of Agriculture and Agricultural Technology, 2024)
The research was conducted to determined sustainable palliative programmes for reducing the impact of corona virus pandemic on food insecurity of crop famers in Taraba State, Nigeria. The specific objectives were to; describe socio-economic characteristics of the crop farmers, determine impactful effects of corona Virus on production efficiencies of the crop farmers and to describe constraints facing the crop farmers before and during the corona virus pandemic. Data for this research were collected using a structured questionnaires administered to 3,000 maize and rice farmers selected via a multi-stage random sampling procedure. Both descriptive and inferential statistics were used to analysed the data collected. The results revealed that majority (64%) of the crop farmers in the study area were males while 54.00% of the respondents were married. The result revealed also revealed that before COVID-19 pandemic, 75% of maize farmers operated on full time basis but during the COVID-19, only 26% operated on full time basis. However, similar trend occurred among the rice farmers where 85% of the farmers were into full time operation before the COVID-19, but only 47% operated during the COVID-19 period. Similarly, maize farmers had an average farm size of 2.30 ha while rice farmers had 2.91ha before the pandemic, but due to lockdown and difficulty in engaging labourers, the average farm size was reduced to 1.03ha and 1.24ha respectively during the outbreak of the pandemic. The major constraints posed by Covid-19 on maize and rice production farmers were; reduction in farm income due to the lockdown (3.72*), inadequate transport facilities to move rice output to the market (3.61*) and fewer hours used in the farm (3.58*). The study conclude that Covid 19 had negative effects on both maize and rice farmers in the study area during the lockdown. The study recommends that Covid-19 protocols should be educated to the maize and rice farmers in the study area in order for them to carry out their maize and rice farming without hindrances.